Предмет: Алгебра,
автор: yazigayazieva
и
С1. Упростите выражение 6(3x-2y)-3(y+x)+2(5x-2y)
найдите его значение при х = –1, y=-2.
Ответы
Автор ответа:
1
6(3x-2y)-3(y+x)+2(5x-2y) = 18х-12у-3у-3х+10х-4у = 25х-19у
Подставляем значения х и у
25*(-1)-19*(-2) = -25+38 = 13
Автор ответа:
1
при х = -1, y = -2
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: Клер11330
Предмет: Английский язык,
автор: samporu89
Предмет: Геометрия,
автор: kostruleva1985
Предмет: Математика,
автор: lisa266